SHADOW ECONOMY, AEOI, DAN KEPATUHAN PAJAK - Dahlan, Muhammad (Scientax, 2020)
This research develops a broad conceptual framework of shadow economy transactions in Indonesia based on the previous research and finds the correlation with the current tax regulation on automatic exchange of information and tax compliance. Shadow economy is the activity of individuals, households, and/or firms that evade, avoid, or not report its transaction to the government. Based on the previous research, by using monetary approach, the average size of shadow economy in Indonesia equals to 8 – 19% of GDP. Based on this data, the government uses automatic exchange of information (AEOI) to minimize the effect of shadow economy to increase tax revenue and to boost tax compliance.